1984
DOI: 10.1002/1097-0142(19840701)54:1<172::aid-cncr2820540132>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of excretory urography, ultrasonography, computerized tomography, and liver and bone scan in the staging of bilharzial bladder cancer in Saudi Arabia

Abstract: The role of ultrasonography, computed tomography (a), and radioisotopic scanning in the staging of bilharzial bladder cancer has not been reported previously. Forty patients with invasive bladder cancer seen at the King Faisal Specialist Hospital and Research Centre between January 1978 and June 1981 underwent complete preoperative workup for staging of their tumors prior to radical cystectomy. The preoperative radiologic investigations included excretory urography (IVP), ultrasonography (US), CT of the pelvis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

1985
1985
1993
1993

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…Subsequent studies [11][12][13][14][15][16][17] have been of a clinical nature. They shed light on some features of the pathology, diagnosis, and epidemiology of the disease.…”
Section: Historymentioning
confidence: 98%
See 1 more Smart Citation
“…Subsequent studies [11][12][13][14][15][16][17] have been of a clinical nature. They shed light on some features of the pathology, diagnosis, and epidemiology of the disease.…”
Section: Historymentioning
confidence: 98%
“…On the contrary, Hanash et al 17 reported 30 patients with bilharzial bladder cancer. Cutajar 15 found that schistosomiasis does not appear to be a significant etiologic factor in urolithiasis, which has a high incidence in Saudi Arabia.…”
Section: Historymentioning
confidence: 99%
“…The authors attributed the difference to the endemicity of schistosomiasis in Asir. Hanash et al 29 reported bilharzial bladder cancer in 30 of 40 bladder cancer patients seen at King Faisal Specialist Hospital (1978)(1979)(1980)(1981).…”
Section: Cancer Of the Bladdermentioning
confidence: 99%
“…Advanced disease was seen in 80%, 85%, 57%, and 71% of bladder, prostate, kidney, and testis, respectively, which compares with the findings of Hanash et al [4].…”
mentioning
confidence: 99%